Development of Speaking Skills Teaching Materials for Japanese Students in Diponegoro State University and Semarang State University - Diner, Lispridona; Zulaeha, Ida; Subyantoro, Subyantoro; Supriatnaningsih, Rina; Utami, Esti Sudi (Lingua Cultura, 2023)
A research showed that the development of students’ basic speaking skills had not reached the expected target. It was important to develop speaking skills by learning materials using Japan Foundation (JF) standards. Speaking skill was communicative competence and mastering language use rather than learning. Speaking, in general, could be intended as a skill to convey one person’s ideas to others by using spoken language. Therefore, the research aimed to address these problems by developing teaching materials for blended learning during a pandemic. It also aimed to develop teaching materials that motivate Japanese students to learn speaking skills independently. Teaching materials were developed following the ADDIE model and tested by learning content and design expert groups. ADDIE of product development were Analysis, Design, Development, Implementation, and Evaluation. Information was collected through class observations and interviews with four Japanese language skills course lecturers. Validation of content and learning design expert tests obtained feasibility of 86% and 91%, respectively. Furthermore, average eligibility for small groups and field testing was 92% and 96%, respectively. The research finds that blended learning-based teaching materials are essential during the pandemic because they increase students’ motivation for physical activities and introduce the use of technology. The research can be developed further to test the application of teaching materials based on blended learning quantitatively.